Participatory Tree Carbon Measurement in Komolchari Village Common Forests in Chittagong Hill Tracts (The Chittagong University Journal of Science, 2021)
Climate change is taking place at a horrifying rate due to the increasing concentration of CO2 in the atmosphere. REDD+ has been considered as a low-cost approach to reducing atmospheric carbon. A study on measurements of tree carbon through a participatory approach was conducted in Komolchari Village Common Forest (VCF) of Khagrachari under the Chittagong Hill Tracts to examine the contribution of local participants in the measurement of tree carbon. From the study, it was estimated that total tree biomass density measured by the forestry experts and the local participants were 147.40±31.26 tha-1and 135.95±27.54 tha-1, respectively, where total carbon density for trees was 73.70±15.63 tha-1and 67.98±13.77 tha-1, respectively. Furthermore, in the case of saplings, the estimated total biomass density measured by the forestry experts and the local participants were 33.63±3.50 tha-1 and 32.41±3.09 tha-1, respectively, where estimated total carbon density for saplings was 16.82±1.75 tha-1and 16.21±1.55 tha-1, respectively. From all of the findings, it was observed that a participatory approach was successfully conducted in the study area to collect data on the measurement of tree carbon. The study will help bring the profit in the carbon trade by reducing transaction costs in the case of collecting data on tree carbon measurement. The findings of the study can be useful for REDD+ implementation in Bangladesh.The Chittagong Univ. J. Sci. 42(1): 1-23, 2020